DIGITAL STORYTELLING AS A TOOL TO IMPROVE WRITING COMPETENCE - Jovliyeva Nafosat Bahodir qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Annotation: This article explores the role of digital storytelling in enhancing writing competence among English as a Foreign Language (EFL) learners. Digital storytelling combines traditional narrative techniques with multimedia tools such as images, audio, video, and text to create meaningful and engaging stories. The study highlights how digital storytelling motivates learners, improves their creativity, and strengthens their ability to organize ideas coherently in written form. It also examines the pedagogical benefits of integrating technology with writing instruction and discusses the challenges teachers may face when applying this method. The findings indicate that digital storytelling is an effective approach to developing writing skills, critical thinking, and digital literacy among EFL students.